The importance of soil drying and re-wetting in crop phytohormonal and nutritional responses to deficit irrigation - Dodd, Ian C.; Puértolas, Jaime; Huber, Katrin; Pérez-Pérez, Juan Gabriel; Wright, Hannah R.; Blackwell, Martin S. A. (Journal of experimental botany, 2015)
Soil drying and re-wetting (DRW) occurs at varying frequencies and intensities during crop production, and is deliberately used in water-saving irrigation techniques that aim to enhance crop water use efficiency. Soil drying not only limits root water uptake which can (but not always) perturb shoot water status, but also alters root synthesis of phytohormones and their transport to shoots to regulate leaf growth and gas exchange. Re-wetting the soil rapidly restores leaf water potential and leaf growth (minutes to hours), but gas exchange recovers more slowly (hours to days), probably mediated by sustained changes in root to shoot phytohormonal signalling. Partial rootzone drying (PRD) deliberately irrigates only part of the rootzone, while the remainder is allowed to dry. Alternating these wet and dry zones (thus re-wetting dry soil) substantially improves crop yields compared with maintaining fixed wet and dry zones or conventional deficit irrigation, and modifies phytohormonal (especially abscisic acid) signalling. Alternate wetting and drying (AWD) of rice can also improve yield compared with paddy culture, and is correlated with altered phytohormonal (including cytokinin) signalling. Both PRD and AWD can improve crop nutrition, and re-wetting dry soil provokes both physical and biological changes which affect soil nutrient availability. Whether this alters crop nutrient uptake depends on competition between plant and microbes for nutrients, with the rate of re-wetting determining microbial dynamics. Nevertheless, studies that examine the effects of soil DRW on both crop nutritional and phytohormonal responses are relatively rare; thus, determining the cause(s) of enhanced crop yields under AWD and PRD remains challenging.